Enhancement of UV photoluminescence in ZnO tubes grown by metal organic chemical vapour deposition (MOCVD). (September 2018) - Iwan, S.; Zhao, J.L.; Tan, S.T.; Sun, X.W.
Abstract: We have synthesized ZnO tubes, without any catalyst, on Al2 O3 (001) substrates by metal organic chemical vapor deposition (MOCVD) at different growth temperatures, pressures and Zn-O ratios. The results confirm that the growth temperature, reactor pressure and Zn-O ratio play important roles in the formation of hexagonal ZnO tubes. Scanning electron microscopy (SEM) images indicated that, at a growth temperature of 500 °C, reactor pressure of 75 Torr and Zn-O ratio of 10/75 are an appropriate condition to obtain hexagonal and well-aligned ZnO tubes. High-resolution, double crystal XRD analysis shows a symmetric ω-scan rocking curve, with a full width at half maximum (FWHM) of 1.1°. It confirms the ZnO tubes have highly c-axis orientation on Al2 O3 substrate. Subsequently, room temperature photoluminescence (PL) studies confirm that the enhancement of UV emissions from ZnO tubes is due to increasing Zn-O ratios. Highlights: The highly c-axis oriented ZnO tubes can be synthesized by MOCVD under appropriate conditions. A growth temperature, reactor pressure, and the Zn-O ratio play an important role to obtain tubular ZnO. The room temperature PL spectrum of ZnO tubes shows the UV enhancement by increasing Zn to O ratio.